CARDIORESPIRATORY FITNESS OF SCHOOLCHILDREN IN ELEMENTARY SCHOOLS IN BELGRADE (Fiep Bulletin - online, 2014)
Cardiorespiratory fitness is one of the most important components of health-related fitness. High cardiorespiratory fitness during childhood and adolescence has been associated with a healthier cardiovascular profile during these years (Mesa et al. 2006 a, b) and later in life (Ruiz et al. 2006a, b). One of the most widely used tests to assess cardio respiratory fitness among children and adolescents is the 20-m shuttle run test (Léger et Lambert, 1982). In the pilot study on the representative sample of schoolchildren of Belgrade (5692 boys and 5358 girls) we examined potential differences in the 20-m shuttle run test between boys and girls, among consecutive grades (from 3rd to 8th grade /9-14 years/). Two-way ANOV A (2x6) were performed (factors: gender and grade). When the significant main effects were found, Bonferroni post-hoc test was performed. The significant main effect of gender (F1,11150 = 872.8; p
Keywords: cardiorespiratory fitness; schoolchildren; elementary school; physical education